Evaluating internal credit rating systems depending on bank size - Hergen Frerichs; Mark Wahrenburg (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
Under a new Basel capital accord, bank regulators might use quantitative measures when evaluating the eligibility of internal credit rating systems for the internal ratings based approach. Based on data from Deutsche Bundesbank and using a simulation approach, we find that it is possible to identify strongly inferior rating systems out-of time based on statistics that measure either the quality of ranking borrowers from good to bad, or the quality of individual default probability forecasts. Banks do not significantly improve system quality if they use credit scores instead of ratings, or logistic regression default probability estimates instead of historical data. Banks that are not able to discriminate between high- and low-risk borrowers increase their average capital requirements due to the concavity of the capital requirements function.
urn:nbn:de:hebis:30-17892
Keywords: G2; G21; G28; C52; 330; Basel II; bank regulation; credit ratings; credit risk; Kreditwürdigkeit; Bank; Kreditrisiko; Basler Akkord; Deutschland; Basler Akkord